Enhancing anthropometric proficiency: Effect of a structured training program on skills of Anganwadi workers in rural areas of Raebareli District, Uttar Pradesh - Mukesh Shukla; Abhay Singh; Sourabh Paul; Mritunjay Kumar; Ravinder Singh Bedi (Journal of Family Medicine and Primary Care)
Context: Anganwadi workers (AWWs) require technical skills for growth monitoring of under-five children. Anthropometric skills help Anganwadi workers assess any changes or deterioration in the normal growth of children. Aims: To determine the effect of a structured training program on the anthropometric skills of Anganwadi workers in rural areas of Raebareli district in Uttar Pradesh. Settings and Design: A community-based interventional study, was conducted among 162 AWWs, 73 from Salon and 89 from Rahi development blocks of Raebareli district. Methods and Material: The skills of AWWs in anthropometric measurement domains (weight, height/length, and mid-upper arm circumference) were assessed using a pre-tested observatory checklist both before and after the training sessions. The skills for each domain were assessed on four points i.e. standard procedure applied to the child, assurance of safety precautions, observer protocol during anthropometry, and precision and accuracy in recording measurement. Statistical Analysis Used: The McNemar Chi-square test was used for paired categorical data analysis. P < 0.05 was considered to be statistically significant. Results: The mean age of the study population was 43.30 ± 9.68 years. The mean years of their job was 16.68 + 7.38 years. About one-fourth (26.5%) of AWWs had received training within the last three years. Inadequate/non-functional equipment (9.8%), low honorarium (29.4%), interruption in timely supply of supplementary food (6.3%), non-cooperation of the community (84.6%), insufficient space (58.0%), and availability of periodic job aids (16.8%) were the major challenges that were faced by ICDS workers. The anthropometric skills of the AWWs were found to improve significantly in almost all the domains. The proportion of AWWs following standard procedure, assurance of safety precautions, observer protocol during anthropometry, precision, and accuracy on recording measurement were found to increase significantly after a structured training program. (P < 0.05). Conclusions: A structured training programme focusing anthropometric skills on play an important role in increasing the skills of AWWs in growth monitoring. AWWs’ capacity to monitor child growth must be refreshed regularly through separate focussed training programs rather than during comprehensive sessions.